RELATIONSHIP BETWEEN THE DEGREE OF URBAN INTELLIGENCE WITH ARTIFICIAL INTELLIGENCE AND FUZZY ALGORITHMS AND THE PERFORMANCE OF ENTERPRISES - Han, Fei (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
This article has comprehensively evaluated the development and evaluation model of intelligent cities on the performance of enterprises in the performance of intelligent cities in the artificial intelligence technology model, established a fuzzy algorithm analysis and evaluation model, and comprehensively evaluated the development level of intelligent cities and the level of performance management in cities. By using AI technologies such as the Internet of Things cloud computing, the intelligent terminals of the whole city are organically integrated to achieve the integration and development of various industries in smart cities and promote the two-way improvement of artificial intelligence and the performance management of enterprises in the city. At the same time as the development advantage of urban enterprises, the development advantage of urban enterprises is more convenient for making human production and living activities in cities through the integration and development of diverse elements and multi-technical fields in life.